(3GdQbGHI GdOSJhQjI Ydi GdeYGgOGJ GdOhdjI (B: s (3OQGSI ebGQfI (B/ s - (3TjeGA YWjI YeGOGdOjf fLes; (3UHQi eMeO GdSfhSi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3Gf GdQbGHI GdOSJhQjI gi GdJi JVef GMJQGe bhGYO GdOSJhQ h JYWjgG GdNUjUI GdbGfhfjI GdJi gi ef Cge NUGFU GdbGYOI GdbGfhfjI(B: (3h GdeJeKdI ai GbJQGfgG HLRGA(B: (3h GdLRGA GdPi jcad ddbGYOI GdOSJhQjI hUa GdbGfhfjI jJeKd ai YOe OSJhQjI GdJTQjY GdeNGda ddbhGYO GdOSJhQjI(B. (3h ef gPG GdefWdb jbUO HQbGHI GdOSJhQjI Ydi GdJTQjYGJ(B: (3QbGHI eOi ehGabI GdJTQjY ddOSJhQ(B. (3h ef Knqe GdeMGaXI Ydi gjHI GdOSJhQ OGNd GdJfXje GdbGfhfi ai GdOhdI(B. (3h RGO ef CgejI GdQbGHI Ydj GdOSJhQjI(B: (3JMhd aj eaghe GdOjehbQGWjI(B: (3de JYO Hg OjehbQGWjI HGdbGfhf Hd OjehbQGWjI HGdOSJhQ h bO JMbb gPG GdGfJbGd (B- (3GdCcKQ OYekG ddOjehbQGWjI (B- (3ef NdGd LgI GdQbGHI Ydj GdTQYjI GdOSJhQjI Ydj GdCNU(B: (3GdJj Jcad dMbhb GdCaQGO h MQjGJge JfGejkG eJUGYOkG jQJbj HfhYjJgG(B: (3jhaQ dMeGjJgG hSGFd GdLRGA GdJj JbGQf CMcGeg(B. (3h JHGTQ LgI GdQbGHI GdbVGFjI Ydi GdOSJhQjI egGegG HGYJHGQgG MGejI ddOSJhQ(B: (3h YdjgG HGdJGdj Cf JMOO fWGb JWHjbg h eYGfjg ef NdGd JaSjQgG(B: (3h jXd GLJgGO LgI GdQbGHI GdbVGFjI Ydi GdOSJhQjI eJhGUdkG aj eLGd JMOjOgG eYGfj GdOSJhQ(B: (3h eJhGdjkG Ydi UYjO EMOGKgG MbhbG LOjOI dG fU YdjgG ajg(B: (3h Ef GYJHQJgG ef ajV bhGYOg dJHJYO CMcGeg TjFkG aTjFkG Yf GdUjZI GdJj CaQZ CUdkG ajgG(B: (3h djXgQ GdOSJhQ aj GdfgGjI h cCfg eLQO XdGd HGgJI ddUhQI GdChdi GdJj cGf YdjgG(B: (3h Ydi GdCNU ef NdGd eHGOF OSJhQjI JVjagG Edi GdOSJhQ(B: (3h cCfgG Jbhe HYedjI Ndb dhKjbI LOjOI dgG edGeM eNJdaI Yf GdUhQI GdJj cGf YdjgG GdOSJhQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B307-322s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdLgI GdeNJUI HGdQbGHI Ydi OSJhQjI GdeYGgOGJ GdOhdjIs; (3GdbjeI GdbGfhfjI ddeYGgOGJ GdOhdjIs; (3WQb GdWYf Ydi OSJhQjI GdeYGgOGJ GdOhdjI aj aQfSGs; (3WQb GdQbGHI Ydi OSJhQjI GdeYGgOGJ GdOhdjI aj eUQs; (3eNGdaI GdeYGgOGJ GdOhdjI ddbhGYO GdOSJhQjI GdELQGFjIs; (3eNGdaI GdeYGgOGJ GdOhdjI ddbhGYO GdOSJhQjI GdehVhYjIs; (3GdeYGgOGJ GdOhdjI hGdTQjYI GdESdGejIs; (3bQGQGJ GdeLdS GdOSJhQj GdaQfSj HTCf GdeYGgOGJ GdOhdjIs; (3CMcGe GdeMceI GdOSJhQjI GdYdjG HTCf GdeYGgOGJ GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes